Synthesis and characterization of a rhodium(I) σ-alkane complex in the solid state. - Pike, S; Thompson, A; Algarra, A; Apperley, D; Macgregor, SA; Weller, A (2012)
Transition metal-alkane complexes-termed σ-complexes because the alkane donates electron density to the metal from a σ-symmetry carbon-hydrogen (C-H) orbital-are key intermediates in catalytic C-H activation processes, yet these complexes remain tantalizingly elusive to characterization in the solid state by single-crystal x-ray diffraction techniques. Here, we report an approach to the synthesis and characterization of transition metal-alkane complexes in the solid state by a simple gas-solid reaction to produce an alkane σ-complex directly. This strategy enables the structural determination, by x-ray diffraction, of an alkane (norbornane) σ-bound to a d(8)-rhodium(I) metal center, in which the chelating alkane ligand is coordinated to the pseudosquare planar metal center through two σ-C-H bonds.